Methylation of BDNF gene in association with episodic memory in women - Alece Arantes Moreno, Ivana; Rodrigues de Oliveira, Daniela; Ribeiro Borçoi, Aline; Fungaro Rissatti, Luciana; Vitorino Freitas, Flávia; Arantes, Lidia Maria Rebolho Batista; Oliveira Mendes, Suzanny; dos Santos Vieira, Tamires; Risse Quaioto, Bárbara; Cerbino Doblas, Paola; Sgrancio Olinda, Amanda; Ribeiro Cunha, Ester; et al. (Frontiers in Neuroscience, 2023)
Brain-derived neurotrophic factor (BDNF) gene regulation plays an important role in long-term memory formation, and the DNA methylation (DNAm) level of BDNF promoters has been associated with episodic memory deficits. Our aim is to explore the association between DNAm levels in BDNF promoter IV with verbal learning and memory performance in healthy women. We conducted a cross-sectional study by recruiting 50 individuals. Episodic memory was assessed by Rey’s Auditory Verbal Learning Test (RAVLT). Clinical interviews, RAVLT, and blood sample collection were assessed in all participants. DNAm was measured on DNA from whole peripheral blood using pyrosequencing. According to generalized linear models (GzLM) analyses, CpG (cytosine guanine dinucleotide) site 5 showed significant associations between Learning capacity (LC, p <0.035), that every 1% of DNA methylation at CpG site 5 results in a 0.068 reduction in verbal learning performance. The current study is the first to show that BDNF DNAm play an important role in episodic memory.